Comparison of coastal tourism destination management against natural disasters of New Zealand and Indonesia - Gulo, Edison Reinkarnasi; Koestoer, Raldi Hendrotoro Seputro (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Coastal tourist destinations have vulnerability to the potential for tsunamis. New Zealand and Indonesia as a coastal tourism destination that facing the risk of natural disasters. This study aims to compare coastal tourism destination management policies against natural disasters in New Zealand and Indonesia. Through the literature review method, this paper analyzes proactive disaster management practices and policies in both countries. New Zealand has developed an efficient early warning system and raised public awareness, while Indonesia has financial challenges and vast areas as obstacles to natural disaster management. Research recommendations include the development of a more responsive early warning system, improved safety education for tourism actors, and greater budget allocation for mitigation projects. These measures are directed at strengthening Indonesia's preparedness in the face of potential natural disasters.